Characterization of ordered aggregates of cerato-platanin and their involvement in fungus–host interactions - Pazzagli, Luigia; Zoppi, Camilla; Carresi, Lara; Tiribilli, Bruno; Sbrana, Francesca; Schiff, Silvia; Pertinhez, Thelma A.; Scala, Aniello; Cappugi, Gianni (Biochimica et biophysica acta, 2009)
The “cerato-platanin family” consists of fungal-secreted proteins that are involved in various stages of the host–fungus interaction and act as phytotoxins, elicitors of defense responses and allergens. Cerato-platanin (CP) is a moderately hydrophobic protein secreted and localized in the cell wall of Ceratocystis platani, the causal agent of a severe disease of Platanus. These properties make CP like the hydrophobins: these are self-assembling proteins that form a surface coating which is involved in the formation of aerial hyphae and in adherence to surfaces. CP aggregation was monitored by ThT, circular dichroism, and AFM. The eliciting activity of CP aggregates was assayed on leaves and cells. The CP self-assembles forming amyloid-like aggregates via a nucleated growth mechanism which is joined up with a cleavage of the N-terminus. The ovoidal shape and the lack of a clear transition toward an all-β structure distinguish these aggregates from typical amyloid fibrils. Moreover, CP aggregates interact with hydrophobic surfaces and enhance the hypersensitive response of Platanus. CP forms “ordered aggregates” for which the soluble prefibrillar structures are the end point of the aggregation process, and do not evolve to insoluble fibrils. An involvement in host–microbe interaction is also suggested.